Heterozygous Recurrent Mutations Inducing Dysfunction of ROR2 Gene in Patients With Short Stature - Gui, Baoheng; Yu, Chenxi; Li, Xiaoxin; Zhao, Sen; Zhao, Hengqiang; Yan, Zihui; Cheng, Xi; Lin, Jiachen; Zheng, Haiyang; Shao, Jiashen; Zhao, Zhengye; Zhao, Lina; et al. (Frontiers in Cell and Developmental Biology, 2021)
Purpose: ROR2, a member of the ROR family, is essential for skeletal development as a receptor of Wnt5a. The present study aims to investigate the mutational spectrum of ROR2 in children with short stature, and to identify the underlying molecular mechanisms. Methods: We retrospectively analyzed clinical phenotype and whole-exome sequencing (WES) data of 426 patients with short stature through mutation screening of ROR2. We subsequently examined the changes in protein expression and subcellular location in ROR2 caused by the mutations. The mRNA expression of downstream signaling molecules of Wnt5a-ROR2 pathway were also examined. Results: We identified 12 mutations in ROR2 in 21 patients, including 10 missense, 1 nonsense and 1 frameshift. Among all missense variants, 4 recurrent missense (c.1675G>A[p.Gly559Ser], c.2212C>T[p.Arg738Cys], c.1930G>A[p.Asp644Asn], c.2117G>A[p.Arg706Gln]) were analyzed by experiments in vitro. The c.1675G>A mutation significantly altered the expression and the cellular localization of ROR2 protein. The c.1675G>A mutation also caused significantly decreased expression of c-Jun. In contrast, other missense variants did not confer any disruptive effect on the biological functions of ROR2. Conclusion: We expanded the mutational spectrum of ROR2 in patients with short stature. Functional experiments potentially revealed novel molecular mechanism that the c.1675G>A mutation in ROR2 might affect the expression of downstream Wnt5a-ROR2 pathway gene by disturbing the subcellular localization and expression of protein.